TERMINASI INOVASI PELAYANAN ANTAR JEMPUT IZIN USAHA MIKRO DAN KECIL DI KECAMATAN BUKIT RAYA KOTA PEKANBARU TAHUN 2019 - Siti Khadijah; Zulfa Harirah MS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Termination Public service innovation for picking up micro and small business permits in Pekanbaru City is a form of conclusion that simplifies public services in licensing related to licensing requirements, procedures, processes, and completion to increase the quality of licensing document services and facilitating and facilitating the community in managing micro and small business licensing. The problem in this research is the high level of slowness, injustice, and high costs. Not to mention the service has not been effective and efficient. The purpose of this study was to find out the termination of the innovation of shuttle service for micro and small business licenses in Pekanbaru City. The research approach used in this study is a qualitative approach and this type of research is descriptive. The location of this research was conducted in Pekanbaru City and data collection techniques were carried out by interviews and documentation. The results of this study are that Termination is a conclusion or dismissal of functions, programs, and policies in public services. The public service for picking up micro and small business licenses has been running and is a public service innovation that makes it easier for the community to apply for business licenses, but in 2019 this innovation has been discontinued. The following are indicators of innovation termination seen from 6 aspects of indicators, namely Development of Innovation Leadership, Development of Innovation culture, Development of Employees, Development of Work Teams and artnerships, Development of Innovation Performance, and Network Development. Keywords: Termination, Public Service, IUMK (Micro and Small Bussines Permit)